Neonatal Brain Abscess with Serratia marcescens after Intrauterine Infection: A Case Report - Mihaela Bizubac; Francisca Balaci-Miroiu; Cristina Filip; Corina Maria Vasile; Carmen Herișeanu; Veronica Marcu; Sergiu Stoica; Catalin Cîrstoveanu (MDPI AG, 2023)
Brain abscesses are a possible complication of bacterial sepsis or central nervous system infection but are uncommon in the neonatal period. Gram-negative organisms often cause them, but Serratia marcescens is an unusual cause of sepsis and meningitis in this age group. This pathogen is opportunistic and frequently responsible for nosocomial infections. Despite the existing antibiotics and modern radiological tools, mortality and morbidity remain significant in this group of patients. We report an unusual unilocular brain abscess in a preterm neonate caused by Serratia marcescens. The infection had an intrauterine onset. The pregnancy was achieved through assisted human reproduction techniques. It was a high-risk pregnancy, with pregnancy-induced hypertension, imminent abortion, and required prolonged hospitalization of the pregnant woman with multiple vaginal examinations. The infant was treated with multiple antibiotic cures and percutaneous drainage of the brain abscess associated with local antibiotic treatment. Despite treatment, evolution was unfavorable, complicated by fungal sepsis (Candida parapsilosis) and multiple organ dysfunction syndrome.